The Individuation Process depicted in Matt Haig's The Midnight Library (2020) - Saputri, Nanda Ika Widyaning (Universitas Negeri Surabaya, 2024)
Psychological growth becomes an essential need to achieve a better quality of life. The way to achieve wholeness and authenticity is individuation. This research examines the individuation process described by Nora Seed in The Midnight Library (2020). The study uses Carl Jung's concept of individuation by emphasizing the role of the personal unconscious and archetypes. The psychological problem of the protagonist's character is despair. Individuation plays the stages of integration by exploring the unconscious, unmasking the persona, accepting the shadow, and acknowledging the animus. Finally, the findings reveal how Nora Seed's individuation process in The Midnight Library can reveal psychological growth from despair to wholeness and authenticity.